Effect of main taste compounds on the release of methoxyphenolic compounds in Pu-erh tea. (15th April 2022) - Ma, Lijuan; Peng, Yuxi; Du, Liping; Zhang, Linqi; Tong, Wenzhe; Weng, Yanru; Xiao, Dongguang; Zhang, Huiling; Huang, Jihong
Abstract: As a typical Chinese tea, Pu-erh tea attracts much attention due to its unique flavor formed by taste and aroma compounds. To study the effects of taste compounds on the aroma release, model solutions containing five typical methoxyphenolic compounds (MCs) and main taste compounds with different concentrations were prepared based on the analysis of Pu-erh tea samples. GC-MS results indicated that the release of five MCs was inhibited by theabrownin, tea polysaccharide, tea polyphenol and catechins. The release of 1, 2-dimethoxybenzene, 3, 4-dimethoxytoluene and 1, 2, 3-trimethoxy-5-methyl-benzene was promoted by gallic acid under a low concentration (≤4 mg/g). Statistically, gallic acid had the most significant effect on the release of MCs. Isothermal titration calorimetry suggested that hydrogen bonds and hydrophobic effects had potential contributions to the interaction between taste and aroma compounds. This work will provide the research basis for revealing the formation mechanism of tea flavor. Highlights: Model was established based on the analysis of Pu-erh tea samples to study the interactions. Theabrownin, catechins, tea polysaccharide and polyphenol inhibited AMC release. Gallic acid affected AMC release most significantly. Release of 1, 2, 3-trimethoxy-5-methyl-benzene was affected most significantly. Interactions between AMCs and the taste compounds were confirmed by ITC.